2005
DOI: 10.1159/000087930
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Correlates of Cerebral White Matter Lesions and Water Diffusion Tensor Parameters in Community-Dwelling Older People

Abstract: DT-MRI parameters, in particular , are sensitive to early ultrastructural changes underlying cognitive ageing. Executive function may be the cognitive domain most sensitive to age-related decline in white matter tract integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 58 publications
5
74
2
Order By: Relevance
“…There existed a significant association between white matter lesion load and severity of DTI and MTR measures in the normalappearing white matter with the microstructural changes in normal brain tissue being more closely related to the patients' clinical presentation than the volume of visible white matter abnormalities [9,32,52,61,69,70,74,92,93]. These observations clearly indicate that age-related small vessel disease of the brain is a diffuse process affecting the entire brain and that white matter lesions are probably only the tip of the iceberg.…”
Section: Age-related White Matter Changes and Normal-appearing Brain mentioning
confidence: 83%
“…There existed a significant association between white matter lesion load and severity of DTI and MTR measures in the normalappearing white matter with the microstructural changes in normal brain tissue being more closely related to the patients' clinical presentation than the volume of visible white matter abnormalities [9,32,52,61,69,70,74,92,93]. These observations clearly indicate that age-related small vessel disease of the brain is a diffuse process affecting the entire brain and that white matter lesions are probably only the tip of the iceberg.…”
Section: Age-related White Matter Changes and Normal-appearing Brain mentioning
confidence: 83%
“…Shenkin et al [25] Subcortical and periventricular WMLs were not associated with any of the cognitive measurements.…”
Section: Reference Associationmentioning
confidence: 92%
“…Based on their proximity to ventricles, WMLs were classified as subcortical or periventricular in seven studies [24][25][26][27][28]33,34]. The results show that more studies have found an association between periventricular WMLs with the cognitive domain of executive function, than subcortical WMLs.…”
Section: Subcortical Vs Periventricular Wmlsmentioning
confidence: 99%
See 2 more Smart Citations